MANAJEMEN PENGORGANISASIAN DAN RUANG LINGKUP DALAM MANAJEMEN PENDIDIKAN ISLAM - Nurul Hikmah; Zakinah Zakinah; Suci Aprilla; Siti Umrah; Sri Muliani Abdullah; Nur Afdalya; Kamus Kamus (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2026)
Islamic education management plays an important role in improving the effectiveness of educational institution management. However, its implementation still faces problems such as weak organizing practices, unclear division of duties, limited coordination among institutional units, and the suboptimal integration of Islamic values into management practices. Previous studies have mostly discussed Islamic education management, organizing, organizational structure, and the scope of management separately, leaving limited attention to their relationship as an integrated conceptual framework. This article aims to explain the concept of Islamic education management, organizational management, organizational structure, and the scope of Islamic education management. This study uses library research with a qualitative descriptive approach by reviewing relevant books, scientific journals, and academic literature. The findings are presented as a conceptual synthesis, not as empirical field research results. This synthesis shows that the effectiveness of Islamic education management is determined by a clear division of duties, authority, and responsibilities; an organizational structure that fits the characteristics of institutions such as schools, madrasahs, and pesantren; and integrated management of curriculum, students, educators, finance, facilities and infrastructure, administration, public relations, supporting units, and extracurricular activities. Islamic values such as trustworthiness, justice, deliberation, responsibility, honesty, and transparency serve as important foundations for building effective governance in Islamic educational institutions and supporting student character formation. Therefore, organizing and managing the scope of Islamic education should be understood as a conceptual strategy to strengthen the quality of Islamic educational institutions. ABSTRAK Manajemen pendidikan Islam berperan penting dalam meningkatkan efektivitas pengelolaan lembaga pendidikan. Namun, pelaksanaannya masih menghadapi masalah berupa lemahnya pengorganisasian, kurang jelasnya pembagian tugas, rendahnya koordinasi antarbagian, dan belum optimalnya integrasi nilai-nilai Islam dalam praktik manajemen. Kajian sebelumnya lebih banyak membahas manajemen pendidikan Islam, pengorganisasian, struktur organisasi, dan ruang lingkup manajemen secara terpisah, sehingga belum banyak menampilkan keterkaitan keempat aspek tersebut sebagai satu kerangka konseptual. Artikel ini bertujuan menjelaskan konsep manajemen pendidikan Islam, manajemen pengorganisasian, struktur organisasi, dan ruang lingkup manajemen pendidikan Islam. Penelitian ini menggunakan metode kepustakaan dengan pendekatan deskriptif kualitatif melalui telaah buku, jurnal ilmiah, dan literatur akademik yang relevan. Hasil kajian ini merupakan sintesis konseptual, bukan hasil penelitian lapangan. Sintesis tersebut menunjukkan bahwa efektivitas manajemen pendidikan Islam ditentukan oleh kejelasan pembagian tugas, wewenang, dan tanggung jawab; kesesuaian struktur organisasi dengan karakter lembaga seperti sekolah, madrasah, dan pesantren; serta pengelolaan terpadu terhadap kurikulum, peserta didik, tenaga pendidik, keuangan, sarana prasarana, administrasi, hubungan masyarakat, unit penunjang, dan kegiatan ekstrakurikuler. Nilai Islam seperti amanah, keadilan, musyawarah, tanggung jawab, kejujuran, dan transparansi menjadi dasar penting dalam membangun tata kelola lembaga pendidikan Islam yang efektif dan berorientasi pada pembentukan karakter peserta didik. Dengan demikian, pengorganisasian dan ruang lingkup manajemen pendidikan Islam perlu dipahami sebagai strategi konseptual untuk memperkuat mutu lembaga pendidikan Islam.